American experience. Grand Coulee Dam [videorecording (DVD)] - Ives, Stephen; Ives, Stephen; Murphy, Michael, 1938- (WGBH/PBS, 2012)
Featuring the men and women who lived and worked at Grand Coulee in the wake of the Great Depression and the native people whose lives were changed alongside historians and engineers, the film explores how the tension between technological achievement and environmental impact hangs over the project's legacy.